2004
DOI: 10.1016/s0889-4906(03)00020-6
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of intonational paragraphs in native and nonnative speaker instructional discourse

Abstract: In the context of classroom communication, there is a premium on the clarity of the message, and instructors will typically employ multiple linguistic cues to highlight information structure. Using a model of intonation in discourse [Brazil, D. (1986). The communicative value of intonation in English. Birmingham, England: University of Birmingham, English Language Research. Brazil, D. (1997). The communicative value of intonation in English. Cambridge: Cambridge University Press.], this paper examines the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 23 publications
0
66
0
1
Order By: Relevance
“…2015. (BRAZIL, 1997), intonation group (CRUTTENDEN, 1986), and intermediate phrase (PIERREHUMBERT;HIRSCHBERG, 1990), is the domain of an intonation contour. Its boundaries were identifi ed by a series of phonetic cues listed in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015. (BRAZIL, 1997), intonation group (CRUTTENDEN, 1986), and intermediate phrase (PIERREHUMBERT;HIRSCHBERG, 1990), is the domain of an intonation contour. Its boundaries were identifi ed by a series of phonetic cues listed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…When the topic comes to an end, there is a lowering of the pitch level and oft en a slowing down, followed by a lengthy pause (YULE, 1980). Another way of describing this phenomenon is to say that pitch range is expanded at the beginning of new topics, then lowered and compressed at the end (BRAZIL; COULTHARD;JOHNS, 1980;PIERREHUMBERT;HIRSCHBERG, 1990). Th ese cues segment discourse into macro-units that are analogous to paragraphs in writing.…”
mentioning
confidence: 99%
“…According to Kang and Pickering (2013), NNS speech tends to be somewhat monotonous because of compressed pitch range and a lack of variety in pitch level choices. Overall narrow pitch range has been identified as the most common feature of NNSs (Pickering 2004, Wennerstrom 1998, especially in East Asian speakers' speech. Studies of Chinese learners pitch range patterns (Hincks & Edlund 2009, Wennerstrom 1998 have shown that Chinese L2 speakers have much more compressed pitch ranges than NS speakers.…”
Section: Methodsmentioning
confidence: 99%
“…Narrow overall pitch range has been identified as the most common intonation feature of NNSs (Pickering 2004, Wennerstrom 1998, especially in East Asian speakers' speech. According to Kang and Pickering (2013), pitch range variation is an important intonation feature that affects NSs' comprehension of NNSs' speech.…”
Section: Pitch Spanmentioning
confidence: 99%
“…Chaudron and Richards' classification of discourse signaling cues pertains to van Dijk's paradigm of discourse structures. [5] compared native-speaker and international teaching assistant's use of pitch and pause cues to create "intonational paragraphs' in their classes. Rickards, et al [6] conducted a research concerning the role of discourse signaling cues in L1 listening comprehension.…”
Section: Generalizationmentioning
confidence: 99%